The Blackbriar genesis - Gervais, Simon (Novelist); Ludlum, Robert, 1927-2001 (G.P. Putnam's Sons, 2022)
When an undercover Treadstone agent is murdered in Prague, but none of his superiors know what he was doing there, Blackbriar operatives Helen Jouvert and Donovan Wade are sent to investigate, drawing them into a world of conspiracy and fake news.